2007
DOI: 10.1063/1.2786021
|View full text |Cite
|
Sign up to set email alerts
|

Frenkel-Poole trap energy extraction of atomic layer deposited Al2O3 and HfxAlyO thin films

Abstract: Frenkel-Poole (FP) trap energies of atomic layer deposited Al2O3 and HfxAlyO thin films with various Hf∕Al compositions have been extracted. Using a method based on the field and temperature dependence of FP conduction, intrinsic trap energies under zero electric field can be extrapolated. Results indicate that FP trap energies increase from 0.56to1.48eV when adding more and more Al to HfO2. The trap energy seems to be inversely proportional to the square of the dielectric constant of the film, suggesting that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(24 citation statements)
references
References 10 publications
3
21
0
Order By: Relevance
“…7 shows a sample Lorentzian fit for the GR spectrum at 450 K. We found that the time constants fall in the range of 80 μs-1 ms within 300-450 K. These values are in agreement with predicted ones in Ref. [6]. The energy level of the traps can be found from the equation 0 exp ,…”
Section: Baseband Noise Vs Residual (Additive) Phase-noise Insupporting
confidence: 83%
See 1 more Smart Citation
“…7 shows a sample Lorentzian fit for the GR spectrum at 450 K. We found that the time constants fall in the range of 80 μs-1 ms within 300-450 K. These values are in agreement with predicted ones in Ref. [6]. The energy level of the traps can be found from the equation 0 exp ,…”
Section: Baseband Noise Vs Residual (Additive) Phase-noise Insupporting
confidence: 83%
“…The driving force behind this is the potential reduction of the gate leakage-current and suppression of the drain-current-collapse, both of which are desired in order to achieve the highest performance from an HFET [2][3][4][5]. However, the oxide layer is not a panacea in that the performance and the reliability of a power device might suffer from the interface and bulk traps associated with the gate oxide layer [6][7][8]. Analysis of these traps can be made easier by bringing to bear new tools in addition to the current-voltage (I-V) and capacitance-voltage (C-V) measurement techniques.…”
mentioning
confidence: 97%
“…4(c). [25][26][27] When V high level < 1.2 V, N T is interface traps (N it ) only. On the contrary, when V high level > 1.2 V, N T is both high-k bulk shallow traps (N hkst ) and N it .…”
Section: Resultsmentioning
confidence: 99%
“…Comparing theory and experimental data we hypothesize that phosphorus vacancies ðV P Þ in the avalanche region are the most probable source of dark counts for 1:06Àmm GM-APDs. The difference in the observed defect energy from DLTS and DCR experiments may be due to Frenkel-Poole barrier lowering caused by the high electric fields in the avalanche layer during DCR testing [11].…”
Section: Resultsmentioning
confidence: 98%